Hubungan Kebudayaan Tafsir Indonesia Analisis Kisah Ibrahim dan Musa dalam Tafsir karya) )Mahmud Yunus, Hamka, dan M. Quraish Shihab - Anwar Mujahidin (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2017)
This study aims to reveal the relationship between cultural background of interpreter with the world of Alquran that is reflected in the interpretation of the story of Abraham and Moses. the research object are three interpretations Indonesia representing the first, second, and contemporary generation, namely The Interpretation of The Koran Karim works of Mahmud Yunus, Tafsir al-Azhar works of Hamka, and Tafsir al-Mishbāh works of M. Quraish Shihab. The methods to analyze the data used text analysis with explanatory analysis approach which describe the structure of the story in the books of tafsir studied and analyzed the correlation structure of the story to the cultural background of the interpreter. The results showed that all three books of commentary which analyzed had different patterns of cultural relations. Tafsir al-Azhar and the interpretation of the Koran Karim more often mentioned stories, religious system, and experiences pointing Indonesian background, while the al-Mishbāh interpretation is that at least mention the background of Indonesian cultural. In addition Tafsir al-Mishbāh also more just describe the common theme groups of verses by absurd and interesting contextuality at the Time of the Prophet, so that the story of Abraham and Moses are less contextual today.